Effect of solvents on the extraction of Kacip Fatimah (Labisia pumila) leaves - Mohd Azrie, A.; Chuah Abdullah, Luqman; Pin, Kar Yong; Tan, H. P. (JOCPR, 2014)
This study aimed to ascertain the effect of solvents on the extraction of some bioactive compound from Kacip Fatimah (Labisia pumila) leaves was investigated. The main compound identified using High Performance Liquid Chromatography was gallic acid. Thus, the solvents tested were water (H2O), ethanol (EtOH), ethyl acetate (EA) and hexane (Hex) as the extraction solvents with 40 °C temperature and four hour extraction time using Solid Liquid Extraction (SLE). Result showed that water was the best solvent for extraction of Kacip Fatimah (Labisia pumila) gave higher yield (13.42 wt. %) followed by ethanol (5.96 wt. %), ethyl acetate (2.46 wt. %) and hexane (1.29 wt. %). This is believed to give good information for particular extraction processes in different polarities of solvents.